Psychometric Characteristics of the CREA in an English Speaking Population - Clapham, Maria M.; Ryan King, W. (Anales de Psicología / Annals of Psychology, 2010)
This study examined the reliability and validity of the CREA, a Spanish measure of divergent thinking, in an English speaking population. Data were collected across two years. During the first year, three forms of the CREA as well as the Verbal and Figural Torrance Tests of Creative Thinking (TTCT), the How Do You Think? (HDYT) inventory, the Runco Ideational Behavior Scale (RIBS), and the NEO were completed by a sample of United States college students across two sessions. In the second year, three forms of the CREA, the Verbal and Figural Torrance Tests of Creative Thinking (TTCT), and the NEO were completed by a sample of the same popula-tion during one session. CREA scores showed strong alternate form but moderately weak test-retest reliability. They correlated significantly and consistently with overall Verbal and Figural TTCT scores, and showed some significant but weak correlations with biographical inventory and extraversion scores, and no association with academic achievement scores. Results demonstrated convergent validity of the CREA with the TTCT, and discriminant validity with measures of other constructs, thus support-ing the use of the CREA as a divergent thinking measure.